Strategi Pengelolaan Wisata Religi Berkelanjutan Untuk Melestarikan Tradisi Masyarakat Islam dan Meningkatkan Perekonomian di Kabupaten Gorontalo - Sabriana Oktaviana Gintulangi; I Kadek Satria Arsana (LPPM Institut Pesantren KH. Abdul Chalim, 2022)
community. Religious tourism villages experience several obstacles, one of which is that the community does not take advantage of these tourist destinations to improve the economy. This study aimed to determine the strategy of managing religious tourism to preserve the traditions of the Islamic community and improve the community's economy. To limit the study of the problems discussed, in this study, the researchers focused more on providing religious tourism infrastructure, strengthening religious tourism institutions, mentoring and promotion, increasing tourism objects and improving the quality of human resources. The data collection techniques used were observation, interviews and documentation. This type of research is descriptive with a qualitative approach. Sources of data used are primary data and secondary data. Data analysis was carried out through the stages of data reduction, data presentation, conclusion drawing and SWOT analysis. The results of this study are a very necessary strategy to develop this tourism object and optimize the power to take advantage of opportunities for religious tourism objects, namely, carry out structured promotions by relying on all social media, improve the quality of human resources, collaborate with village governments and local communities and empower, counselling to grow and increase public awareness and tourism management about the importance of tourism awareness.